MODELING OF HYDROMECHANICAL DRIVE SYSTEM OF WORKING BODY FOR MOBILE TECHNOLOGY MACHINE - A. R. Temirkanov,; A. T. Rybak (Advanced Engineering Research)
An element of the working body (brush) of the aerodrome sweeper – a synchronous hydromechanical drive – is considered. It is based on the throttle flow divider of the non-spool type plunger setters, and it is driven by two hydraulic motors. Its mathematical model is offered. Special attention is given to describing the stress state of the brush shaft when twisting under the variable load, and to identifying the effect of the shaft elastic properties on the dynamic properties of the synchronous hydromechanical system. In this paper, modeling of the synchronous hydromechanical brush drive system, unlike the conventional method, is based on the use of the reduced volume stiffness of the hydraulic system. This simplifies the modeling and allows performing a rapid analysis of the test drive operation which significantly reduces the design time of the drive system with the given performance properties.